Infants show systematic rhythmic motor responses while listening to rhythmic speech - Boll-Avetisyan, Natalie; Shandala, Arina; Langus, Alan (Frontiers in Psychology, 2024)
Rhythm is known to play an important role in infant language acquisition, but few infant language development studies have considered that rhythm is multimodal and shows strong connections between speech and the body. Based on the observation that infants sometimes show rhythmic motor responses when listening to auditory rhythms, the present study asked whether specific rhythm cues (pitch, intensity, or duration) would systematically increase infants’ spontaneous rhythmic body movement, and whether their rhythmic movements would be associated with their speech processing abilities. We used pre-existing experimental and video data of 148 German-learning 7.5- and 9.5-month-old infants tested on their use of rhythm as a cue for speech segmentation. The infants were familiarized with an artificial language featuring syllables alternating in pitch, intensity, duration, or none of these cues. Subsequently, they were tested on their recognition of bisyllables based on perceived rhythm. We annotated infants’ rhythmic movements in the videos, analyzed whether the rhythmic moving durations depended on the perceived rhythmic cue, and correlated them with the speech segmentation performance. The result was that infants’ motor engagement was highest when they heard a duration-based speech rhythm. Moreover, we found an association of the quantity of infants’ rhythmic motor responses and speech segmentation. However, contrary to the predictions, infants who exhibited fewer rhythmic movements showed a more mature performance in speech segmentation. In sum, the present study provides initial exploratory evidence that infants’ spontaneous rhythmic body movements while listening to rhythmic speech are systematic, and may be linked with their language processing. Moreover, the results highlight the need for considering infants’ spontaneous rhythmic body movements as a source of individual differences in infant auditory and speech perception.